2019
DOI: 10.1111/jebm.12341
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hip fracture in patients on hemodialysis versus peritoneal dialysis: A meta‐analysis of observational studies

Abstract: Background: Bone and mineral metabolism disorders are common among end-stage renal disease (ESRD) patients, which could lead to hip fracture. It is unclear whether the hip fracture risk is different among patients on hemodialysis (HD) versus peritoneal dialysis (PD). This meta-analysis was conducted to evaluate the hip fracture risk in ESRD patients on HD, when compared to PD. Methods: A literature review was conducted in EMBASE, MEDLINE, and Cochrane databasesthrough January 31, 2018 to identify studies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…The screening and extraction of data were conducted separately by two independent reviewers [ 23 ]. In opposing views between the two reviewers, a third reviewer [ 24 , 25 ] was invited to reconcile the differences. Duplicate articles were detected and removed using EndNote X8 software (Thomson Corporation; Stamford, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The screening and extraction of data were conducted separately by two independent reviewers [ 23 ]. In opposing views between the two reviewers, a third reviewer [ 24 , 25 ] was invited to reconcile the differences. Duplicate articles were detected and removed using EndNote X8 software (Thomson Corporation; Stamford, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…If not, a third assessor would help to resolve the arguments. 20,21 Two investigators reviewed the titles and abstracts of all records and identified studies potentially eligible for inclusion, which received a full-text evaluation if meeting our inclusion criteria. The following data of each study were extracted: first author’s name; year of publication; study designs; sample size; diagnostic criteria; mean/median age; races; gender; disease duration; follow-up period; treatments and concomitant medications of interventions/comparisons; AE-associated populations; particular populations (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…5,14,23 For example, peritoneal dialysis has been shown to have a lower rate of hip fractures and have a beneficial effect compared with hemodialysis on bone mineral density during first year of therapy. 4,17 Limitations of this study largely stem from its retrospective nature. Large portions of patients with CKD are undiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…5,14,23 For example, peritoneal dialysis has been shown to have a lower rate of hip fractures and have a beneficial effect compared with hemodialysis on bone mineral density during first year of therapy. 4,17…”
Section: Discussionmentioning
confidence: 99%